Maṯnawī ḏū baḥrain : maʿrūf ba Mirʾāt al-ʿirfān = Mirʾāt al-ʿirfān - ʿĀrif, ʿAli Akbar Šīrāzī (Nawal Kišūr, 1897)
Narrative poem by an Iranian scholar who travelled to India, settled in Lakhnaʾū, and took up service in the court of Naṣīr ad-Dīn Ḥaidar. Contains autobiographical elements as well as a description of Lakhnaʾū and its ruler